Research on Online Ideological and Political Education in Universities from the Perspective of Big Data - Dan, Xu (Journal of Theory and Practice of Contemporary Education, 2023)
In the work system of ideological and political education in universities, universities should do a good job in ideological and political work, use the dissemination form of modern network media big data to effectively promote ideological and political work, and form a combination of high-tech information technology, national responsibility, historical mission, and other ideological and political education work. Online ideological and political education is a review of the Party's struggle process. The reason why we can constantly experience difficulties and hardships, create new brilliance, is very important. It is to build high-quality theories of the Party with the trend of development, strengthen the Party's adherence to arming our Party members and cadres with scientific theories, and use this as the foundation of ideological and political education, continuously deepening and expanding the teaching methods and content of ideological and political education in universities. Continuously enhance students' interest in learning ideological and political education, enabling them to continuously optimize their own innovative thinking while also moving towards the correct direction of ideology, politics, and values.